1986
DOI: 10.1107/s0108768186098270
|View full text |Cite
|
Sign up to set email alerts
|

Electron charge density and electron momentum distribution in magnesium oxide

Abstract: The electronic structure of magnesium oxide is presented and discussed, as resulting from a LCAO crystalline-orbital Hartree-Fock extended-basis-set computation. Mulliken populations, charge density maps, structure factors, electron momentum distribution 0108-7681/86/030247-07501.50and Compton profiles are provided. They are compared with the results of simple theoretical models, and with available experimental data. The present study confirms the fully ionic character of MgO; it also shows that there is a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In addition, the coupling of the size of the oxygen ion to the Madelung potential provides a many-body force which produces a Cauchy violation [Mehl et al, 1986]. More recently, Causa et al [1986b] found that Hartree-Fock charge densities for MgO were in good agreement with the ionic model with Note that there is no hybridization between any of the oxygen states and states on the magnesium. For the B2 structure, the gap is indirect from M to F at low pressures and becomes direct at M at high pressures.…”
Section: Equation Of State and High-pressure Propertiesmentioning
confidence: 98%
“…In addition, the coupling of the size of the oxygen ion to the Madelung potential provides a many-body force which produces a Cauchy violation [Mehl et al, 1986]. More recently, Causa et al [1986b] found that Hartree-Fock charge densities for MgO were in good agreement with the ionic model with Note that there is no hybridization between any of the oxygen states and states on the magnesium. For the B2 structure, the gap is indirect from M to F at low pressures and becomes direct at M at high pressures.…”
Section: Equation Of State and High-pressure Propertiesmentioning
confidence: 98%
“…This effect becomes especially prominent for the nearcutoff harmonics. The angular width of the maxima along the Mg-O bonding direction is ∼10 • , which approximates the angle subtended by the O atom to the Mg atom considering their atomic radii 19 .…”
mentioning
confidence: 99%
“…In order to clarify electronic and chemical properties of the average structure we determined the valence-electron density distribution using the density-functional theory (DFT hereafter) formalism (Hohenberg & Kohn, 1964;Kohn & Sham, 1965). It is an established fact that the electron density distribution determined by ab initio approaches such as Hartree±Fock calculations (Causa et al, 1986) or DFT (Charlier et al, 1991) fall within the experimental error bar of X-ray determinations. In a complementary study of the average structure of calaverite (Gonze et al, 2001) we determined the equilibrium geometry within the DFT.…”
Section: Introductionmentioning
confidence: 81%